First Language Lexical Attrition in a First Language Setting: A Multi-Measure Approach Testing Teachers of English - Ma, Yueqingzhou; Vanek, Norbert (Journal of psycholinguistic research, 2024)
Research on first language (L1) attrition typically focuses on immigrant populations in their second language (L2) environment, yet we know comparably little about L1 attrition in the L1 setting. This study used two lexical tasks to test L1 attrition, a time-sensitive word decision task and a video retelling. Chinese teachers of English vs. Chinese teachers of other subjects ( N = 25/group) were recruited at a secondary school in China. The aim was to provide an exploratory basis of the L2 influence on L1 lexical attrition in the L1 environment, both on the level of lexical comprehension and production. Mixed-effects models were used to analyse multiple measures including response accuracy and reaction times in comprehension, and lexical diversity, density, sophistication, and accuracy in production. The results showed Chinese teachers’ L1 lexical attrition in the form of longer response times to high-frequency Chinese words compared to non-English Chinese teachers, and the use of significantly fewer sophisticated words in their retellings. Also, teachers of English were faster and more accurate in decisions about Chinese borrowings from English, suggesting L2-driven influence on their mental lexicon. Considering participants’ background information, analyses showed that increased L2 exposure and frequency of use can predict L1 lexical attrition.